Nanotechnology: A Potential Weapon to Fight against COVID-19 - Tiwari, Atul K; Mishra, Anupa; Pandey, Govind; Gupta, Munesh K.; Pandey, Prem C. (John Wiley and Sons Inc, 2022)
The COVID-19 infections have posed an unprecedented global health emergency, with nearly three million deaths to date, and have caused substantial economic loss globally. Hence, an urgent exploration of effective and safe diagnostic/therapeutic approaches for minimizing the threat of this highly pathogenic coronavirus infection is needed. As an alternative to conventional diagnosis and antiviral agents, nanomaterials have a great potential to cope with the current or even future health emergency situation with a wide range of applications. Fundamentally, nanomaterials are physically and chemically tunable and can be employed for the next generation nanomaterial-based detection of viral antigens and host antibodies in body fluids as antiviral agents, nanovaccine, suppressant of cytokine storm, nanocarrier for efficient delivery of antiviral drugs at infection site or inside the host cells, and can also be a significant tool for better understanding of the gut microbiome and SARS-CoV-2 interaction. The applicability of nanomaterial-based therapeutic options to cope with the current and possible future pandemic is discussed here.
This paper is submitted by the author of IIT (BHU), Varanasi, India
Keywords: Targeted drug delivery; Nanostructured materials; Antiviral agents; Chemical detection; Controlled drug delivery; Diseases